81 Integrating A Front Door Frailty Service in the Emergency Department: Results of A Pilot Study. (16th March 2021) - Dunnell, L; Shrestha, A; Li, E; Khan, Z; Hashemi, N
Abstract: Introduction: Increasing old age and frailty is putting pressure on health services with 5–10% of patients attending the emergency department (ED) and 30% of patients in acute medical units classified as older and frail. National Health Service improvement mandates that by 2020 hospital trusts with type one EDs provide at least 70 hours of acute frailty service each week. Methodology: A two-week pilot (Monday–Friday 8 am-5 pm) was undertaken, with a "Front Door Frailty Team" comprising a consultant, junior doctor, specialist nurse and pharmacist, with therapy input from the existing ED team. They were based in the ED seeing patients on arrival, referrals from the ED team and patients in the ED observation ward—opposed to the usual pathway of referral from the ED team to medical team. Data was captured using "Cerner" electronic healthcare records. A plan, do, study, act methodology was used throughout with daily debrief and huddle sessions. Results: 95 patients were seen over two weeks. In the over 65 s, average time to be seen was 50 minutes quicker than the ED team over the same period, with reduced admission rate (25.7% vs 46.5%). The wait between decision to admit and departure was shortened by 119 minutes. Overall, this led to patients spending on average 133 minutes less in the ED. 64 patients were discharged, of which 44 had community follow-up (including 37.5% of 64 referred to acute elderly clinic and 25% to rapid response). 47 medications were stopped across 25 patients. Conclusion: The pilot shows that introduction of an early comprehensive geriatric assessment in the ED can lead to patients being seen sooner, with more timely decisions over their care and reduction in hospital admissions. It allowed for greater provision of acute clinics and community services as well as prompt medication review and real time medication changes.